Can antibiotic use be both just and sustainable… or only more or less so? - Millar, Michael (Journal of medical ethics, 2011)
Antibiotic resistance threatens the capacity to treat life-threatening infections. If it is accepted that it will be many years (if not decades) until the production of new antibiotics overcomes current concerns with antibiotic resistance then ways to conserve the effectiveness of current antibiotics will have to be found. For many bacterial agents of infection levels of antibiotic resistance are directly dependent on the quantity of antibiotic prescribed. Antibiotics are currently underutilised in many parts of the world. If a just distribution of access to antibiotics requires equal access for individuals with equal need irrespective of wealth then responding to this requirement of justice has the potential to shorten the effective life of currently available antibiotics. Increasing the range and numbers of individuals treated with antibiotics would seem to threaten sustainability and also potentially undermine the access of future generations to cost-effective treatments for bacterial infection. The control of antibiotic resistance requires that the determinants of infectious disease transmission are addressed, such as poor housing, education and nutrition as well as the provision of antibiotics. The apparent tension between intragenerational justice and sustainability diminishes when the account of distributive justice extends beyond access to antibiotics and includes plural entitlements. Controlling antibiotic resistance requires more than the redistribution or reduction (in the overall use) of antibiotics.